Dispersing Properties Of Tanning Agents And Possibilities Of Their Use In Flotation Of Fine Minerals - G. Rinelli; A. M. Marabini (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1980)
A wide-ranging series of experiments has been carried out on value minerals (sphalerite, smithsonite and hematite) and gangue minerals (quartz and calcite) to assess the properties of various commercially available vegetable and synthetic tannins as dispersants for these minerals in a finely ground state (<5 microns). Experiments to determine the dispersing power of each reagents on every mineral have been performed through sedimentation tests run first in water and afterwards in the presence of a collector having specific action on the mineral concerned. The tests have been extended to a wide range of dispersant concentrations, maintaining the pH and collector concentrations at the levels known to be the best for the flotation of the various minerals. By comparing the results obtained on each mineral, conclusions have been drawn on the possibility of using different classes of vegetable and synthetic tannins in the selective flotation of fine particles. These results have been related to the structure of the tanning compounds and to the surface properties of the minerals.